(x+8)(x+4)=60

Simple and best practice solution for (x+8)(x+4)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(x+4)=60 equation:



(x+8)(x+4)=60
We move all terms to the left:
(x+8)(x+4)-(60)=0
We multiply parentheses ..
(+x^2+4x+8x+32)-60=0
We get rid of parentheses
x^2+4x+8x+32-60=0
We add all the numbers together, and all the variables
x^2+12x-28=0
a = 1; b = 12; c = -28;
Δ = b2-4ac
Δ = 122-4·1·(-28)
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-16}{2*1}=\frac{-28}{2} =-14 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+16}{2*1}=\frac{4}{2} =2 $

See similar equations:

| n/4-9=7 | | m=(5,0)(5-20) | | 1/6x+1/8x=23/8 | | 145=-2/3x-51 | | 5p=£35 | | 4x+-12=10 | | 117=5^x-8 | | 2n−3=1 | | 3-(4-x)=55 | | 7x+8x-9x-5=37 | | 8x+24=4x+26 | | (27+1)=(5y+4) | | 268=-w+164 | | M-7=2x9 | | X+0.825x=216.50 | | n/20=3/5 | | 0.123-2=x | | 13k-(27)=12 | | n/20=3/5. | | 5(x+6)+11ū=25-3x | | 81=9h | | 5t-4=-19 | | 2x−32x+6=3/4 | | 13y=190 | | 12+3/7x=18 | | 9m-6=5m+26 | | f/9-20=-25 | | 2(x-1)=2x-17 | | 0.2(x+4)=2/10x+3 | | 6•(3x+4)=5•(2x+8) | | 2x5+5x=16/15 | | 5-(6x+2)-3=6 |

Equations solver categories